2009
DOI: 10.1086/600303
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of a Rapid Real‐Time Polymerase Chain Reaction Assay for Universal Intrapartum Group B Streptococcus Screening

Abstract: This real-time PCR assay is a highly accurate test to identify intrapartum GBS carriers at point of care. This new tool could enhance the exact identification of candidates for intrapartum antibiotic prophylaxis, including women with preterm rupture of membranes or preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 28 publications
6
147
5
1
Order By: Relevance
“…Rapid real-time PCR assays for GBS detection have been further developed and their performances have been evaluated these last years as summed up in Table 2. When compared to enriched GBS cultures, sensitivity and specificity for PCR tests range from 62.5%-100% and 84.6-100% while PPV and NPV range from 65-100% and 92.3-100% [80,82,[84][85][86][103][104][105][106][107][108][109][110][111]. Today, real-time PCRbased tests (NAAT) can equal or surpass the sensitivity of antenatal culture at 35-37 weeks' gestation and compare favorably with reference to bacterial culture performed at presentation for delivery taken as gold standard for the detection of GBS colonization [80,82,101,102,112].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid real-time PCR assays for GBS detection have been further developed and their performances have been evaluated these last years as summed up in Table 2. When compared to enriched GBS cultures, sensitivity and specificity for PCR tests range from 62.5%-100% and 84.6-100% while PPV and NPV range from 65-100% and 92.3-100% [80,82,[84][85][86][103][104][105][106][107][108][109][110][111]. Today, real-time PCRbased tests (NAAT) can equal or surpass the sensitivity of antenatal culture at 35-37 weeks' gestation and compare favorably with reference to bacterial culture performed at presentation for delivery taken as gold standard for the detection of GBS colonization [80,82,101,102,112].…”
Section: Non-culture Methods For Intrapartum Specimen Processingmentioning
confidence: 99%
“…However the expected predictive values were too optimistic. In studies evaluating antenatal culture to predict intrapartum status for genital colonization with GBS, reported sensitivities range from 51% to 87%, specificities from 93.7% to 97.1%, positive and negative predictive values from 60.6% to 87% and from 88% to 96% [77,[79][80][81][82][83][84][85][86][87].…”
Section: Timing Of Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Xpert Ò GBS targets the same gene as IDI-Strep B TM and provides even better results than the latter assay [18]. In 2009, a French study showed that the intrapartum test with Xpert Ò GBS was highly sensitive and specific and provided a much higher positive predictive value for intrapartum GBS colonization (97.8 %) than antenatal cultures (58.3 %) [7]. These results should be interpreted with caution, because antenatal cultures were not performed as recommended to reach optimal sensitivity, thus favoring the sensitivity of PCR and lowering the positive predictive value of antenatal cultures.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…Nevertheless, several studies have shown a low sensitivity of antenatal GBS cultures to detect colonization during labor [7][8][9]. Cases of EOD in infants born at term have occurred among mothers with negative antenatal GBS culture results and it has been reported that at least 10 % of this group of women turned positive at labor [10].…”
Section: Introductionmentioning
confidence: 99%